PENGELOLAAN LIMBAH MINYAK PELUMAS SEBAGAI UPAYA PENGENDALIAN PENCEMARAN LINGKUNGAN - Veza Azteria; Ruslan Abdul Gani (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2020)
PT. Astra International Tbk recorded the demand for the use of lubricants as one of the spare parts components sought by Honda motorcycle consumers to continue to increase where at the end of 2015 lubricant parts sales were recorded at 18,596,521 lubricants and each month on average they needed around 1,149,125 lubricant (Gani, 2016). In the case of waste producers, B3 waste management can be transferred to other parties accompanied by documents showing evidence of delivery of B3 waste, in accordance with the contents of Article 32 Paragraph (2) Government Regulation Number 101 of 2014. The meaning transferred here can be interpreted as being sold to another party, because the waste of used lubricating oil still has economic value. This study aims to determine the process of managing lubricating oil waste at Astra Motor Balikpapan. This study was designed as a descriptive observational evaluation study conducted cross sectionally by observing, analyzing, observing and processing data and information that has been systematically collected. The results showed that the management of used lubricant waste at Astra Motor Balikpapan was quite good, but there were some things that needed to be improved including control from Balikpapan BLHD supervision, workshops and continuous counseling and the absence of strict administrative sanctions.